Manufacturer and Foreign Distributor Business Relationship - Zysk, Lukasz (My University, 2008)
In the time of rapidly growing globalisation and economic integration a successful business relationship is what companies strive for. Partners have to recognise that a relationship is a complicated process with many dimensions. This research discusses a successful long-term business relationship between a manufacturer and its foreign distributors. The main research question is: “How can successful long-term business relationship between a manufacturer and its foreign distributor be established? The purpose of the study is to investigate the relationship from both the manufacturer and foreign distributor point of view. In the theoretical part the process of partner selection was described together with process phases and process criteria. Secondly, relationship dimensions such as: types, stages, levels and elements were described with the most important of these being: conflict, commitment, communication and information exchange, co-operation, power, trust and personal contact. Findings show how a successful long-term relationship between foreign distributors and manufacturer can be established, what factors influence the establishment and how the partner selection process influences the long-term relationship.
Keywords: Relationship; foreign distributor; manufacturer; manufacturer-distributor relationship; partner selection criteria